Interprofessional Care Conferences for High-Risk Primary Care Patients. (June 2016) - Weppner, William G.; Davis, Kyle; Sordahl, Jeffrey; Willis, Janet; Fisher, Amber; Brotman, Adam; Tivis, Rick; Gordon, Tim; Smith, C. Scott
Abstract : Problem: As health care systems convert to team-based care, the need to improve interprofessional education is tremendous. In addition to formal instruction, trainees need authentic team-based workplace learning experiences. Approach: The authors designed the PACT-ICU (Patient-Aligned Care Team Interprofessional Care Update) conference to provide team-based care to high-risk patients while teaching trainees principles of interprofessionalism and modeling relevant behaviors. Trainees, supervisors, and affiliated support staff from the fields of internal medicine, nurse practitioner, pharmacy, psychology, and nursing all participate in this conference. During the conference, each participant focuses on the narrative of the patient's illness from his/her own professional perspective. A multifaceted care plan with specific action items is the product of the conference. To evaluate this workplace learning opportunity, the authors recorded patient characteristics, plus trainees' participation and satisfaction. Outcomes: Over the first 16 months (2013–2014) of the PACT-ICU, 33 trainees presented 79 patients. Each trainee presented two or three times each academic year. Patients were 90% male; their mean age was 64.5 years (SD 9.3, range 28–92), and their mean calculated 90-day risk of death or hospitalization was 22% (SD 14%, range 1%–45%). Overall, all surveyed trainees (n = 32; 97% response rate) expressed satisfaction, reporting that the conference was "helpful" or "very helpful" in developing treatment plans. Next Steps: Further assessment of change in trainee behavior related to interprofessional team care, patient-level outcomes (e.g., quality of care and utilization), and factors facilitating dissemination of the model to other academic clinic settings is necessary.